Extracellular Proteases of Mucor pusillus - Khan, M. R. (1979)
Mucor pusillus was grown in different media for a period of 92 h, and the media were investigated for both milk-clotting and protease activities. It was observed that the ratio of extracellular milk-clotting activity to protease activity was the highest for 3% corn steep liquor containing 1% glucose as the source of carbon. Variation of both milk-clotting and protease activities was studied during the growth of the organism in the medium stated above. Separation of protease was carried out by ion-exchange chromatography at pH 8.0. Fractions collected were assayed for both activities simultaneously. The findings suggested that, instead of only one major acid protease, as reported by previous workers, two major acid proteases were produced. One of them had significant rennin-like activity, and the other lacked it. The former could be assumed to be the enzyme reported and studied by previous workers. The existence of two proteases was further confirmed by the appearance of two protease activity bands on polyacrylamide gels after electrophoresis. An attempt was made to separate the rennin-like enzyme from nonspecific protease activity by ammonium sulfate fractionation followed by ion-exchange chromatography at pH 6.0. The results indicated that the nonspecific protease activity due to the enzyme that lacked rennin action was substantially removed by the ammonium sulfate fractionation.